2023
DOI: 10.1080/15592294.2023.2299044
|View full text |Cite
|
Sign up to set email alerts
|

Plasma methylated GNB4 and Riplet as a novel dual-marker panel for the detection of hepatocellular carcinoma

Yanteng Zhao,
Lei Zhao,
Huifang Jin
et al.

Abstract: Early detection of hepatocellular carcinoma (HCC) can greatly improve the survival rate of patients. We aimed to develop a novel marker panel based on cell-free DNA (cfDNA) methylation for the detection of HCC. The differentially methylated CpG sites (DMCs) specific for HCC blood diagnosis were selected from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases, then validated by the whole genome bisulphite sequencing (WGBS) of 12 paired HCC and paracancerous tissues. The clinical performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Therefore, healthy white blood cells were used as controls in tissue validation for this study. They were also used as controls in other studies [ 42 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, healthy white blood cells were used as controls in tissue validation for this study. They were also used as controls in other studies [ 42 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that combining Cell-free DNA (cfDNA) methylation-specific high-throughput or MSP testing with serology enhances the accuracy of serological assays of alpha-fetoprotein (AFP) alone during early screening for HCC. 40 …”
Section: The Role Of Dna Associated Methylation In Hccmentioning
confidence: 99%
“…Several studies have shown that combining Cell-free DNA (cfDNA) methylation-specific highthroughput or MSP testing with serology enhances the accuracy of serological assays of alpha-fetoprotein (AFP) alone during early screening for HCC. 40 In targeted therapy of HCC, DNA methyltransferases (DNMT) and DNA demethylases (ten-eleven translocation, TET) in methylation modification may play an important role. In cancer stem-like cells (CSCs), coordinated activation of DNMT3a and TET2 triggers and maintains drug resistance, which would be a therapeutic target for refractory HCC.…”
mentioning
confidence: 99%
“…1 New cases of HCC in China, a high-risk country for HCC, accounted for 45.3% of all new HCC cases worldwide in 2022. 2 Early detection of liver diseases is crucial, as it correlates with an enhanced 5 year relative survival rate and prognosis. 3 In clinical practice, serum biomarkers such as aspartate aminotransferase (AST), alkaline phosphatase (ALP), and alanine aminotransferase (ALT) are commonly employed to reflect the pathological status of the liver, which is the main method for liver function detection at present.…”
Section: Introductionmentioning
confidence: 99%